2021
DOI: 10.1038/s41598-020-79322-x
|View full text |Cite
|
Sign up to set email alerts
|

National trends in cardiovascular health metrics among Iranian adults using results of three cross-sectional STEPwise approaches to surveillance surveys

Abstract: To examine the trends of 7 cardiovascular health metrics (CVH metrics) incorporate of smoking, physical activity, diet, body mass index (BMI), fasting plasma glucose (FPG), total cholesterol (TC), and blood pressure (BP) level during three cross-sectional STEPwise approaches to surveillance (STEPS), 2007–2016, among Iranian adults. The study population consisted of 19,841 women and 17,243 men, aged 20–65 years. The CVH metrics were categorized as ‘ideal’, ‘intermediate’, and ‘poor’. The sex-stratified weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…Both populations were at an elevated risk of acquiring fatal cardiovascular disease within 10 years (23.9% of Saudi students and 16.7% of Egyptian students) ( 27 ). In Iran despite the slight recession in the number of smokers, total cholesterol, and blood pressure, adverse trends in physical activity, unhealthy diet, obesity, and fasting plasma glucose must be addressed immediately at a public health level in order to battle the advancement of CVDs ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both populations were at an elevated risk of acquiring fatal cardiovascular disease within 10 years (23.9% of Saudi students and 16.7% of Egyptian students) ( 27 ). In Iran despite the slight recession in the number of smokers, total cholesterol, and blood pressure, adverse trends in physical activity, unhealthy diet, obesity, and fasting plasma glucose must be addressed immediately at a public health level in order to battle the advancement of CVDs ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the STEPwise study in Iran, although the prevalence of ideal CVH metrics among the population aged 20 to 65 years old reached about 7.2% in 2011, it again decreased to <4% in 2016 (24).…”
Section: Discussionmentioning
confidence: 82%
“…Physical activity (PA): adults ≥ 20 years, “Poor = None, Intermediate = < 600 MET mins/week, 600–< 1500 MET mins/week, and ≥ 1500 MET mins/week, based on the Global Physical Activity questionnaire 19 , 32 . (Adults ≥ 20 years, “Poor = None, Intermediate = 1–149 min/wk moderate intensity or 1–74 min/wk vigorous intensity or 1–149 min/wk moderate + vigorous, ideal = ≥ 150 min/wk moderate intensity or ≥ 75 min/wk vigorous intensity or ≥ 150 min/wk moderate + vigorous”).…”
Section: Methodsmentioning
confidence: 99%
“…We could not find any trend study on ideal CVH in East and South Asian countries, with the exception of a study in North China, which however, does not report the total ideal CVH metrics 18 . In a trend study over ten years in Iran, the prevalence of 5–7 ideal CVH metrics slightly reduced from 22.7% in 2007 to 19.5% in 2016, the mean CVH metrics increased from 4.7 in 2007 to 5.0 in 2016 19 . In a trend study among adults in USA over seven years the prevalence of the ideal CVH score significantly increased from 3.89 in 2011 to 3.96 in 2017 20 , and a trend study over 20 years in France found a decrease in ideal CVH 21 .…”
Section: Introductionmentioning
confidence: 97%